A short-cut graphical method for sizing of recycle valves in anti-Surge system considering time delay. (October 2017) - Oh, Yutaek; Lee, Chul-Jin; Lim, Youngsub
Highlights: We propose a short-cut graphical method to size anti-surge valves. The method can reflect the valve characteristics and the time delays quantitatively. The method is simple and practical to size multiple valves without a surge. The method can avoid oversizing of recycle valves economically. Abstract: A surge in a centrifugal compressor can cause critical damage to the compressor, resulting in large repair costs, so one of the most important considerations in the design of compressor systems is to prevent a surge. However, conventional methods to size recycle valves in anti-surge systems are limited in that the valve characteristics and time delay cannot be quantitatively considered. This paper suggested a short-cut graphical method to easily size the recycle valves in an anti-surge system by considering the valve characteristics, including the dead time, actuation time, and opening types. Dynamic simulations were carried out to verify the resulting size of the valves, and the results of the simulation showed that a surge could be avoided effectively and economically.